Analisis Proses Berpikir Siswa Pada Materi Persamaan Kuadrat Berdasarkan Kemampuan Penalaran Matematis - Inayah, Hikmi; Madawistama, Sri Tirto (Sahabat Publikasi, 2024)
Students' mathematical reasoning skills are very important in understanding mathematical concepts and solving mathematical problems. The lack of students' reasoning ability can affect student learning outcomes that do not reach the target so it needs to be honed in order to realize appropriate learning outcomes. The purpose of this research is to find out students' thought process in solving quadratic equation problems based on mathematical reasoning ability. The type of research used is qualitative research, and uses a descriptive approach. The source of data in this research is class IX students totaling 22 students with the subject selected 3 students. The data analysis technique in this research is qualitative data analysis. From the test results of students' mathematical reasoning abilities are categorized based on the assessment reference. Researchers categorized it into 3 categories, namely high, medium, and low. Based on the results of tests and interviews, students in the high category can fulfill 4 indicators well. Students in the medium category were only able to fulfill indicators 1 and 2 well, for indicator 3 could not be fulfilled well so they could not fulfill indicator 4. Subject 3 in the low category was only able to fulfill indicator 2 well. Indicators 1 and 3 were not well met.